2019
DOI: 10.1007/s10620-019-05763-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Cannabis of Potential Value as a Therapeutic for Inflammatory Bowel Disease?

Abstract: Cannabis is commonly used by patients with inflammatory bowel disease (IBD) to ameliorate their symptoms. Patients claim that cannabis reduces pain, increases appetite, and reduces the need for other medications [1-3]. The prevalence of cannabis use in patients with IBD is 15-40% [4], including among pediatric patients [5]. Nevertheless, few scientifically sound data exist regarding the value of cannabis in the treatment of IBD. This discrepancy between the patient's perception of cannabis as an effective medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(11 reference statements)
0
4
0
Order By: Relevance
“… 16 These results are consistent with decreased endocannabinoid levels being associated with increased colitis in humans, and relevant therapeutically in that endocannabinoids (and cannabis) are increasingly being explored for potential therapeutic activity against IBD. 16 , 17 , 65 …”
Section: Discussionmentioning
confidence: 99%
“… 16 These results are consistent with decreased endocannabinoid levels being associated with increased colitis in humans, and relevant therapeutically in that endocannabinoids (and cannabis) are increasingly being explored for potential therapeutic activity against IBD. 16 , 17 , 65 …”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with decreased endocannabinoid levels being associated with increased colitis (Diab et al, 2019). Endocannabinoids (and cannabis) are increasingly being explored for potential therapeutic activity against IBD (Cani et al, 2016; Naftali, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our evaluation of the evidence, neither disease showed any improvement in response or remission. The use of marijuana as a drug to treat inflammatory bowel disease still requires much larger, well-designed drug trials [ 18 ]. In the current state, evidence-based medicine would recommend against its use as a treatment, given the lack of efficacy shown in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…While marijuana may not be effective as a pharmacologic therapy for disease management, it may have a role as an adjunct to standard therapy [ 18 ]. Some studies have reported improvements in pain and overall improved disease outlook when patients took marijuana or its derivatives [ 6 , 7 , 12 ].…”
Section: Discussionmentioning
confidence: 99%